Gonorrhoea in women in Scotland. Evidence of cohorts having a higher or lower incidence than expected. Issue 4 (August 1979) - Schofield, C B
Abstract : Incidences of genital gonorrhoea in women higher or lower than expected occurred in patients aged 15--19 years four years after similar findings in those aged 10--14 years. This pattern was followed five years later in those aged 20--24, 11 years later in those aged 25--34, and 20 years later in those aged 35--44 years. Thus, cohorts of women at greater or lesser risk of acquiring gonorrhoea appear to exist. Most cohorts with a high incidence could be identified when in the 10--14 age group. Especially high rates of infection are predicted in the 25--34 age group in the mid-1980s and in the 35--44 age group in the late 1980s. These findings will affect the timing of health education on sexually transmitted diseases in schools and will demand a high degree of awareness among general practitioners, gynaecologists, and those working in family planning and well-women clinics of the possibility of gonorrhoea occurring in women in these age groups.